Kolaborasi Pekerja Tenun Songket Dengan Perajin Sebagai Inovasi Industri Kreatif Desa Gelgel, Klungkung - Ni Komang Arini Styawati; Anak Agung Rai Sita Laksmi; I Made Mardika; I Ketut Kasta Arya Wijaya; Ni Wayan Sitiari; I Gusti Putu Ghosadhira Vedhastama (Postgraduated Community Service Journal, 2023)
Gelgel Village is famous for its production of Balinese woven fabrics, namely songket and endek fabrics. Songket/endek cloth is one of the characteristics of Balinese cultural products. However, the production of songket woven cloth did not develop much. The demand for the production of songket woven fabric in Gelgel Klungkung Village is still low. This is because the production is only in the form of kamen, shawls, and headbands, there are no new creations, so demand only increases when there are certain ceremonies such as wedding ceremonies and Hindu religious ceremonies. Songket cloth has a unique characteristic pattern. Now that business competition is getting tougher, there are already many fabric manufacturers that are similar to songket at a lower price. There needs to be collaboration between songket weavers and artisans in an integrated manner. Songket woven fabric as one of the cultures of the Gelgel people needs to be preserved by providing a form of legal protection. The problems experienced by partners are: 1) The demand for the production of songket woven fabric in Gelgel Klungkung Village is still low. What are the efforts that can be made to create innovations to attract buyers' interest in the production of songket woven fabrics in Gelgel Village? 2) With increasingly fierce business competition, what efforts can be made in the business of distributing songket production in Gelgel Village in the face of competitors in the weaving business? 3) The problem of Human Resources (HR) is also an obstacle for the songket business in Gelgel Village, because there is no younger generation who want to become weavers in Gelgel Village?.